Saccharomyces cerevisiae HS-1와 Streptococcus thermophiles HS-2 함유 복합 미생물비료 처리 후 크리핑 벤트그래스의 생육 - 김영선; Young-sun Kim; 이긍주; Geung-joo Lee (Hanguk hwangyeong nonghak hoeji, 2023)
This study was conducted to evaluate the effects of soil microbial fertilizer (SMF) containing Saccharomyces cerevisiae HS-1 and Streptococcus thermophiles HS-2 on the growth of creeping bentgrass. For the pot experiment, the treatments were as follows: no fertilizer (NF), control (3 N g/m 2 /month), SMF-1 (control+SMF 2 mL/ m 2 /time), and SMF-2 (control+SMF 4 mL/m 2 /time). For the plot experiment, the treatments were as follows: NF, control, SMFp-1 (control+SMF 1 mL/m2/time), SMFp-2 (control+SMF 2 mL/m2/time), and SMFp-3 (control+ SMF 4 mL/m 2 /time). In the pot experiment, visual turfgrass quality and the uptake amount of nitrogen (N) and potassium (K) were increased under the SMF treatments, whereas the content of chlorophyll (a, b, and a+b) and clipping yield were not considerably different compared with the control. In the pot experiment, the amount of SMF positively correlated with visual turfgrass quality and uptake amount of N and K. In the plot experiment, turfgrass density was increased by 12.9-19.2% under SMFp treatments compared with the control. These results indicated that the application of SMF containing Sa. cerevisiae HS-1 and St. thermophiles HS-2 improved the quality, density, and growth of creeping bentgrass via prompting the uptake of N and K.